Income inequality and economic growth: the reexamination of the existence of Kuznets curve: evidence from CEE countries - Kuźmar, Sławomir (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: In the last years, a lot of attention has been paid to economic inequality — a phenomenon that may lead to what some commentators predict as the end of capitalism. At the same time some economists believe that the economic inequalities are natural and excessive inequalities can be reduced through the process of economic growth. The natural starting point in the discussion concerning the relation between inequality and economic growth is the theory proposed by Simon Kuznets, according to which inequality rises in the early phases of economic development but falls eventually as the growth advances, taking the shape of the inverse-U shaped pattern. The empirical validity of the so-called “Kuznets curve” has been intensively investigated, but the evidence is ambiguous. In this context re-examining Kuznets theory in CEE countries is interesting especially because of the observed rapid economic growth as a result of structural transformation in these countries. Aim: The aim of the study is an attempt to investigate the nature of relation between economic growth and income inequality levels in Central and Eastern Europe (CEE) countries in years 2004–2020 and verify if the analysed relation is taking an inverse-U shape as indicated by the Kuznets curve. Results: The results of conducted analysis indicate that the evidence for an inverted-U shaped relation between inequality levels and economic growth in CEE countries is much less robust than what is implied by Kuznets curve theory.